2014
DOI: 10.1371/journal.pone.0089845
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Lean Fish Reduces the Risk of Type 2 Diabetes Mellitus: A Prospective Population Based Cohort Study of Norwegian Women

Abstract: BackgroundThe effects of fish consumption and n-3 fatty acids on type 2 diabetes mellitus (T2DM) have recently been debated.ObjectiveWe explored the risk of T2DM in relation to consumption of lean fish, fatty fish, fish products and total fish as well as cod liver oil supplements in a representative sample of Norwegian women.DesignThis was a prospective population based cohort study in 33740 women free of T2DM, stroke, angina or heart attack and with detailed information on important co-variates and dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…The beneficial effects of fish consumption on both CVD [6,7,8,9,10,11,12] and DM2 have been described previously [13,14,15]. Since MetS consists of several of the same risk factors as CVD and DM2, one would expect fish consumption to reduce the risk of MetS as well.…”
Section: Introductionmentioning
confidence: 81%
“…The beneficial effects of fish consumption on both CVD [6,7,8,9,10,11,12] and DM2 have been described previously [13,14,15]. Since MetS consists of several of the same risk factors as CVD and DM2, one would expect fish consumption to reduce the risk of MetS as well.…”
Section: Introductionmentioning
confidence: 81%
“…In infants, this index was suggested to be a more important marker of the fatty acid status than the absolute amounts of fatty acids [23,38]. In some [39][40][41], but not all [42,43] observational studies, fish consumption has been associated with a lower risk of diabetes. Whether the possible beneficial effects of fish consumption are attributable to long-chain n-3 fatty acids or to other components of fish remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the possible beneficial effects of fish consumption are attributable to long-chain n-3 fatty acids or to other components of fish remains unclear. In the prevention of type 2 diabetes, the consumption of lean fish may be even more beneficial than the consumption of fatty fish [41]. Instead, fish oil supplementation might have adverse effects on glucose metabolism, including increased gluconeogenesis and impaired insulin secretion and insulin sensitivity [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Shellfish consumption has been specifically addressed in six studies, also providing heterogeneous results suggesting inverse [13], direct [6] or no association [5, 7, 12, 41] with type 2 diabetes risk. Five cohort studies distinguished between lean and fatty fish: one showed a weak inverse association with fatty fish but not with lean fish [41], one observed higher risk associated with lean fish but not with fatty fish [7], one observed an inverse association with lean fish but not with fatty fish [14], and two did not observe statistically significant associations [6, 12]. …”
Section: Discussionmentioning
confidence: 99%